An Overview of the Thermal Energy Sector in Romania - Mihail Busu (International Journal of Advanced Science and Technology, 2020)
The public service of thermal energy supply includes all the activities regarding the production, transport, distribution and supply of the thermal energy carried out at the level of the administrative-territorial units, in order to provide the thermal energy needed to heat and prepare the hot water for consumption for the population, public institutions, social objectives- cultural and economic operators. The present study makes an analysis of the evolution of the thermal energy market in Romania. The public service of thermal energy supply is presented and a descriptive analysis of the thermal energy production, distribution and supply during 2014 to 2016 is presented. Results and conclusions of the paper are in line with other research papers in the thermal energy area, worldwide and at the European Union level